Report of the governor and committee of the Hudson's Bay Company [electronic resource] : to be laid before the shareholders on Tuesday, June 27th, 1882. - Hudson's Bay Company. ([London : s.n.], 1882)
Tables. Electronic reproduction. Mode of access: Internet. 44